Peranan institusi keagamaan dan Institusi Pengajian Tinggi Awam (IPTA) dalam menganalisis isu bioetika : ke arah pembentukan panduan kapada pengguna bioteknologi di Malaysia / Rasmuna Mazwan Muhammad - Muhammad, Rasmuna Mazwan (2011)
Advancements in science and technology particularly in the field of biotechnology and medicine have given rise to various ethical and moral challenges. In Malaysia, these challenges require deliberation which incorporates the scientific and the religious enterprise. This study documents the various processes involved. It shows that bioethics assessment of issues such as genetically-modified food (GMF), the use of porcine enzyme (in livestock), the use of botox, organ transplantation and stem cell treatment is better addressed by the close collaboration of scholars from the Department of Islamic Development Malaysia, the Selangor Mufti Department and the Institute of Islamic Understanding Malaysia with members of the academia of the various public institutions of higher learning (IPTA). Bioethical issues are systematically addressed with specific focus of three indicators namely – the formulation and issuance of Fatwa (religious decree), the process of Halal certification and the reliability of the source of information. The findings show that contrary to popular belief, religious authorities do not deliberate fatwa exclusively without the involvement of external quarters but rather it is complemented by scientific evidence afforded by academic experts from IPTA together with the contributions of relevant institutions such as the Ministry Of Health, National Department of Chemistry and Malaysian Agriculture Research and Development Institute.